Pegada hídrica verde no Espírito Santo - Andrade, Maria Sueliane Santos de (2017)
The water footprint is a relatively new concept of freshwater appropriation that considers its direct and indirect use by a consumer or producer and is used as a comprehensive indicator of the appropriation of water resources. The present study aimed to estimate the green water footprint and evaluate its sustainability in the state of Espírito Santo. The calculation of the total green water footprint was estimated based on the Water Footprint Assessment Manual and using the land use information in the state. The assessment of the sustainability of the green water footprint was calculated using indicators of water scarcity. The total green water footprint was estimated by the sum of the green water footprints of pasture, forest, coffee, forestry and other agricultural uses. The most representative land uses, covering 82.3% of the state area, were: pasture (46.0%), including macega (4.3%); native forest (21.9%), including initial regeneration stage (6.3%) and restinga (0.3%); coffee (8.6%); and eucalyptus (5.8%). The total green footprint estimated was 47 billion m³/year, and the pasture class represented 49% of this consumption, forest 30%, coffee 10%, forestry 6%, and other agricultural crops only 5%. The environmental sustainability assessment of the green footprint was unsustainable for most of the year, on average, mainly in the months of May to September, with the highest green water scarcity index in June.